Penatalaksanaan Holistik Pada Pasien Tuberkulosis Anak Usia 2 Tahun Di Puskesmas Pasar Ambon Melalui Pendekatan Kedokteran Keluarga - ASY SYADZALI; Reni Zuraida (Medula, 2021)
Tuberculosis (TB) is a disease caused by infection with the bacterium Mycobacterium tuberculosis in the lungs. This disease usually attacks the lungs (pulmonary TB) but can also affect other organs (extrapulmonary TB). This study is a case report with analysis of primary data obtained through history taking, physical examination and home visits to complement family data, psychosocial and environmental data. Secondary data were obtained from the patient's medical record at the puskesmas. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. Patient An. N, 2 years old with TB and poor nutritional status, so there needs to be an intervention to improve the patient's nutritional status to support the success of TB treatment. In this case, a diagnosis of tuberculosis was made in accordance with the theory and technical guidelines for the management and management of TB in children, the Ministry of Health of the Republic of Indonesia. The management of category 1 pulmonary tuberculosis given was in accordance with evidence based medicine. After the intervention, there was a decrease in clinical symptoms and behavioral changes in the patient's family, seen after the family was given the intervention and finally understood better to motivate the patient and always remind and accompany the patient when taking medication, as well as providing food with balanced nutrition to the patient. The management given to the patient was in accordance with the technical instructions for the management and management of TB in children, the Ministry of Health of the Republic of Indonesia.